Zn and Se protect toxic metal mixture-mediated memory deficit by activation of Nrf2-hmox-1 signaling in the hippocampus of female rats - Dike, Chinyere S.; Orish, Chinna N.; Ezejiofor, Anthonet N.; Umeji, Theresa C.; Cirovic, Ana; Cirovic, Aleksandar; Orisakwe, Orish E. (Rzeszów University Press, 2025)
Introduction and aim. Heavy metals mediate neurotoxicity by altering some signaling pathways. This work investigated the effect of two nutritional elements Zn and Se on neurotoxicity caused by toxic metals. Material and methods. Female Sprague Dawley rats (35) were divided in to 5 groups (7 rats/group), treated as follows: orally received deionized water (group I), heavy metals mixture HMM: 20 mg·kg -1; 0.40 mg·kg -1 of Hg; 0.56 mg·kg -1 of Mn; and 35 mg·kg -1 of Pb body weight; of Al (group II), HMM+Zn (zinc chloride; 0.80 mg·kg -1) (group III), HMM+Se (sodium selenite: 1.50 mg·kg -1) (group IV) and HMM+Zn+Se (group V). Before euthanasia of the rats, the Cincinnati Dry Maze, Barnes Maze, and Rotarod tests were performed. After euthanasia, the hippocampus was examined biochemically and histopathologically. Results. Treatment with HMM induced inflammation with increased concentration of interleukin 6 and tumor necrosis factor α (30.70±6.65, p<0.02 pg/mg protein and 14.20±4.81 pg/mg protein, p<0.0001) respectively, compromised antioxidants levels, potentiated lipid peroxidation (higher malondialdehyde at 0.94±0.04 nmol/g tissue, p<0.0001 and nitric oxide at 3.89±0.16 nmol/g tissue, p<0.0001 levels), disrupted Nrf2 signaling pathway, potentiated acetylcholinesterase activity and induced mild pathohistological alterations in the rat hippocampus. Conclusion. Supplementation with Zn and Se attenuated HMM mediated neurotoxicity.
Ethical approval was given by the University of Port Harcourt Research Ethics Committee (UPH/PUTOR/REC/12).
Keywords: heavy metal mixture; essential trace elements; neurotoxicity; neurobehavioral testing; oxido-inflammation